ISPC Commentary on the PIM Phase II Preproposal (2017-2022) - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2015)
ISPC Commentary on the Policies, Institutions, and Markets (PIM) Phase II Preproposal (2017-2022)